EFFECTS OF PILE-SOIL INTERACTION ON THE STRUCTURAL INTEGRITY OF OFFSHORE JACKET PLATFORM - Lim, Xiu Yi (Universiti Teknologi PETRONAS, 2018)
On Malaysia waters, half of over 200 numbers of offshore jacket platforms have surpassed the designed lifespan of 25 years. The life continuity of jacket platforms is threatened by environmental loads e.g. wave, current, and soil loading which can cause structural failure of the jacket members. Hence, the safety of offshore platforms in Malaysia incited great concern from the oil and gas corporates. To save company’s spending on Strengthening, Modification and Repairing (SMR) works, reliability analysis serves as an appropriate tool for structural safety assessment. This project studies the effect of pile-soil interaction (PSI) on the structural integrity of offshore jacket platforms to provide inclusion of pile-soil interaction into a structural reliability analysis of a jacket platform in Kumang oil field of Sarawak, Malaysia.